Evolution of Frequency and Intensity of Concurrent Heavy Precipitation and Storm Surge at the Global Scale: Implications for Compound Floods - Lai, Yangchen; Li, Qingquan; Li, Jianfeng; Zhou, Qiming; Zhang, Xinchang; Wu, Guofeng (Frontiers in Earth Science, 2021)
Compound flood raised from the concurrent heavy precipitation and storm surge receives increasing attention because of its potential threat to coastal areas. Analyzing the past changes in the characteristics of compound flood events is critical to understand the changing flood risks associated with the combination of multiple drivers/hazards. Here, we examined the evolution of the compound flood days (defined as days of concurrent extreme precipitation and extreme storm surge exceeding the 90th percentiles) based on the observed precipitation and storm surge data across the globe. Results showed that the annual number of compound flood days increased significantly by 1–4 per decade (α=0.1) on the east coast of the US and northern Europe, while the annual number of compound flood days decreased significantly in southern Europe and Japan. The increasing trends in precipitation under extreme storm surge and storm surge under extreme precipitation were found extensively across the world except in Japan, suggesting that more intense precipitation appeared when extreme storm surges occurred, and higher storm surge emerged when extreme precipitation occurred. Comparatively, the global fractional contributions of storm surge (i.e., 65%) on changes in compound flood days were higher than that of precipitation (i.e., 35%), demonstrating that storm surge was more likely to dominate the changes in the number of compound flood days. This study presented the spatial and temporal characteristics of the compound flood events at the global scale, which helps better understanding the compound floods and provides scientific references for flood risk management and an indispensable foundation for further studies.